2015
DOI: 10.1007/s00415-015-7927-9
|View full text |Cite
|
Sign up to set email alerts
|

Nerve ultrasound in the differentiation of multifocal motor neuropathy (MMN) and amyotrophic lateral sclerosis with predominant lower motor neuron disease (ALS/LMND)

Abstract: The objective of the study was to investigate nerve ultrasound (US) in comparison to nerve conduction studies (NCS) for differential diagnosis of amyotrophic lateral sclerosis with predominant lower motoneuron disease(ALS/LMND) and multifocal motor neuropathy(MMN). A single-center, prospective, examiner-blinded cross-sectional diagnostic study in two cohorts was carried out. Cohort I: convenience sample of subjects diagnosed with ALS/LMND or MMN (minimal diagnostic criteria:possible ALS (revised EL-Escorial cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 22 publications
2
50
0
4
Order By: Relevance
“…This finding was confirmed by a recent report employing high resolution sonography in MMN patients (3,15,16), but its utility for differential diagnosis, especially in MMN patients without solid diagnostic evidence (e.g., CB and/or anti-ganglioside antibodies), had been little explored. We have thus demonstrated that, in patients with otherwise typical MMN but no overt CB, sonography can provide evidence of demyelination.…”
Section: Discussionsupporting
confidence: 68%
“…This finding was confirmed by a recent report employing high resolution sonography in MMN patients (3,15,16), but its utility for differential diagnosis, especially in MMN patients without solid diagnostic evidence (e.g., CB and/or anti-ganglioside antibodies), had been little explored. We have thus demonstrated that, in patients with otherwise typical MMN but no overt CB, sonography can provide evidence of demyelination.…”
Section: Discussionsupporting
confidence: 68%
“…Based on previous results, we expected to find a relationship between PGRN and CSA with the demographic data. As, indeed, CSF PGRN / Q alb , serum PGRN and CSA values were related to age, sex, height, and weight (for details, see the Results section), standardized regression residuals of those variables after regression on baseline age, sex, height, and baseline weight were used for bivariate correlations hypothesized to be found between CSF PGRN / Q alb , serum PGRN and CSA.…”
Section: Methodsmentioning
confidence: 98%
“…High‐resolution ultrasound is a useful tool to quantify structural nerve pathology and thus has a role in the diagnostic workup of peripheral nerve disorders, such as hereditary and immune‐mediated neuropathies . Recently, nerve sonography has been applied to amyotrophic lateral sclerosis (ALS) demonstrating evidence of both nerve root and distal peripheral nerve atrophy; this offers potential for ultrasound‐based differentiation of ALS and ALS‐mimicking disorders characterized by enlarged nerves, particularly multifocal motor neuropathy . Thus far, sonographic nerve measures, however, have failed to show robust associations with clinical data and other biomarkers in ALS, such as disease duration, revised ALS Functional Rating Scale (ALSFRS‐R), disease progression rate, and electrophysiological data .…”
mentioning
confidence: 99%
“…By contrast, in MMN, ultrasonography can detect enlargement of nerves at sites that are not clinically involved 94 , although the enlargement in cross-sectional area has a weak correlation with electrophysiological findings 95 . Nevertheless, ultra sonography might help to differentiate MMN from lower motor neuron disease 96,97 , as enlarged nerves or roots are more common in MMN.…”
Section: Notalgiamentioning
confidence: 99%